The effect mechanism of ergosterol from the nutritional mushroom Leucocalocybe mongolica in breast cancer cells: Protein expression modulation and metabolomic profiling using UHPLC-ESI-Q - Asmaa Hussein Zaki; Bao Haiying; Mohamed Mohany; Salim S. Al-Rejaie; Bahaa Abugammie (Elsevier, 2024)
The ergosterol from mushrooms has gained significant ethnopharmacological importance in various cultures, including China, Japan, and Europe. This compound has been found to possess immune-boosting and anti-inflammatory properties, making it useful in the treatment of immune disorders. In this study, we focused on investigating the potential anticancer properties of ergosterol isolated from the edible mushroom Leucocalocybe mongolica in breast cancer cell lines. The ergosterol was purified and identified using advanced analytical techniques such as ESI-MS and NMR. We conducted cell proliferation assays on 4 T1 breast cancer cells to assess the cytotoxic effects of ergosterol. Furthermore, we analyzed the transcription levels of BAX, caspase-7, BCL-2, STAT-3, and PARP proteins using real-time PCR and Western blot analysis. Additionally, we employed non-targeted ultra-high-performance liquid chromatography and high-resolution mass spectrometry (UPLC-MS/MS) to study the potential mechanisms underlying the anticancer effects of ergosterol at the metabolomics level. The results demonstrated a significant reduction in cell viability and the induction of apoptosis upon treatment with ergosterol, especially at higher concentrations (P < 0.05). Moreover, ergosterol affected the expression of cancer-related genes, upregulating pro-apoptotic proteins such as BAX, caspase-7, and PARP, while downregulating the anti-apoptotic proteins BCL-2 and STAT-3 (P < 0.05). Western blot analysis confirmed these findings and provided further evidence of ergosterol's role in inducing apoptosis. Metabolomics analysis revealed substantial changes in pathways related to amino acid, antioxidant, and carbohydrate metabolism. In conclusion, our study demonstrates that ergosterol exhibits anticancer effects by inducing apoptosis and modulating metabolic pathways in breast cancer cells.